2009
DOI: 10.3168/jds.2009-2282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the in vitro susceptibility of bovine mastitis pathogens to a combination of kanamycin and cefalexin: Recommendations for a disk diffusion test

Abstract: Cows suffering from bovine mastitis have markedly reduced milk production because of inflammation within the udder subsequent to infection and damage from bacterial toxins. Antibiotic treatment is commonly used as a preventative and therapeutic measure for bovine mastitis. The most common pathogens include Staphylococcus aureus, various streptococci (Streptococcus dysgalactiae, Streptococcus uberis), and coliforms (Escherichia coli), which can be contracted from other infected cows or from the environment. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…aureus veterinary isolates were determined to be framycetin-susceptible. The high degree of susceptibility of staphylococci to aminoglycosides observed with mastitis isolates was consistent with other veterinary surveillance studies (Gentilini et al, 2000;Erskine et al, 2002;Makovec and Ruegg, 2003;Aarestrup and Schwarz, 2006;Pillar et al, 2009;Silley et al, 2012). In contrast, penicillin resistance among these isolates ranged from 26.4% with CNS to 31.2% with Staph.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…aureus veterinary isolates were determined to be framycetin-susceptible. The high degree of susceptibility of staphylococci to aminoglycosides observed with mastitis isolates was consistent with other veterinary surveillance studies (Gentilini et al, 2000;Erskine et al, 2002;Makovec and Ruegg, 2003;Aarestrup and Schwarz, 2006;Pillar et al, 2009;Silley et al, 2012). In contrast, penicillin resistance among these isolates ranged from 26.4% with CNS to 31.2% with Staph.…”
Section: Resultssupporting
confidence: 89%
“…Using an ECOFF of 4 μg/mL for framycetin as determined by the overall MIC distribution ( Figure 2C), 98.2% of isolates were determined to be framycetin-susceptible. The levels of aminoglycoside susceptibility observed with veterinary isolates of E. coli is consistent with that observed in other veterinary surveillance studies (Erskine et al, 2002;Lehtolainen et al, 2003;Makovec and Ruegg, 2003;Wallmann et al, 2003;White, 2006;Pillar et al, 2009). As expected, penicillin had little to no activity alone against E. coli.…”
Section: Resultssupporting
confidence: 88%
“…For this study, cefalexin : kanamycin ratios and concentrations were derived from available PK data. Following infusion into the mammary gland the cefalexin : kanamycin concentration ratio changes in vivo from ratio 1·5 : 1 (original concentrations in the intramammary syringe) at time of drug administration, to 1·25 : 1 after 3 h, further to 1 : 2·3 after 6 h and c. 1 : 10 after 12 h (Pillar et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, cefalexin : kanamycin ratios and concentrations were derived from available PK data. Following infusion into the mammary gland the cefalexin : kanamycin concentration ratio changes in vivo from ratio 1AE5 : 1 (original concentrations in the intramammary syringe) at time of drug administration, to 1AE25 : 1 after 3 h, further to 1 : 2AE3 after 6 h and c. 1 : 10 after 12 h (Pillar et al 2009). The study from Ganiere and Denuault (2009), which investigated the in vitro bactericidal activity of the combination at a fixed ratio of 1AE5 : 1, indicated that the combination mainly exhibits a concentration-dependent bactericidal activity and that complete kill of major mastitis pathogens could be achieved within 4-6 h. Ganiere et al, however, did not show whether the same killing rates could be achieved even if the ratio of the two antibiotics is changing.…”
Section: Discussionmentioning
confidence: 99%
“…Although stress and physical injuries may be other causes of inflammation of the udders, infections by bacteria or other microorganisms remain the major cause [51,52]. The most common aetiological agents include Staphylococcus aureus, various streptococci (Streptococcus dysgalactiae, Streptococcus uberis), and coliforms (Escherichia coli), which can be contracted from other infected cows or directly from the environment [53,54]. In response to bacterial infiltration in dairy cows, there are two major forms of inflammation of the mammary glands: clinical and subclinical mastitis.…”
Section: Mastitis Inflammationmentioning
confidence: 99%